Medication Adherence among Mentally Ill Patients with comorbid- Substance Use Disorder - Jahan, Nasim; Maruf, Mohammad Muntasir; Hossain, Md Faruk; Chowdhury, Md Waziul Alam; Begum, Anwara (KYAMC Journal, 2017)
Substance misuse is usually associated with poorer psychiatric medication adherence among mentally ill patients. Identifying proportion & predictors of medication adherence among patients with dual psychiatric and substance misuse problems is important because poor adherence is associated with relapse and re-hospitalization. This study was a descriptive cross sectional study conducted among the patients dually diagnosed with psychiatric and substance use disorders attending OPD in a tertiary care hospital of Dhaka city, during the period from May 2013 to November 2013. The main objective of the study was to explore the proportion of psychotropic medication adherence among the respondents who were on such medication for at least last 6 months (N=151). Respondents were selected purposefully. An informed consent was taken from the patients or care givers and data were collected using the questionnaire designed by the researcher based on Factors Influencing Neuroleptic Medication Taking Scale (FNIMTS). Diagnoses were done previously according to DSM-IV TR by psychiatrist appointed in inpatient and outpatient department. Questionnaire was filled up by the researcher by interviewing the patients and attending care givers as needed. Over half of the respondents (57.0%) admitted they had missed taking their medications on more than one occasion in the week prior to the interview. Thus this study found the proportion of medication adherence to be 43% among the respondents. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 602-609